초등학교 4학년 다문화가정 아동의 집단괴롭힘 피해경험이 학교생활적응에 미치는 영향: 자아탄력성에 의한 문화적응 스트레스의 조절된 매개효과 - 이은경(Eun Gyoung Lee); 이선희(Sun-Hee Rhee) (Korean Journal of child studies, 2019)
Objectives: This study aimed to investigate the influence of acculturative stress and ego-resiliency on the relationship between peer victimization and school adjustment of children in multi-cultural families. Specifically, the mediating effect of acculturative stress and the moderating effect of ego-resiliency were examined in the relationship between peer victimization and school adjustment. Methods: The research subjects for the first year panel survey conducted by the National Youth Policy Institute were 1,635 children of multi-cultural families completed self-report questionnaires designed to assess peer victimization, acculturative stress, ego-resiliency, and school adjustment. Data were analyzed for the moderated mediating effect between variables using PROCESS Macro methods. Results: First, acculturative stress partially mediated the relationship between peer victimization and school adjustment. Second, ego-resiliency significantly moderated the relationship between peer victimization and acculturative stress. Namely significantly suggested that peer victimization was more weakly associated with acculturative stress as ego-resiliency was strengthen. Lastly, the mediating effect of acculturative stress was moderated by ego-resiliency in the relation between peer victimization and school adjustment. Conclusion: Methods are suggested to improve school adjustment of children from multi-cultural families KCI Citation Count: 9